Dublin City University New Library – A Library for the Information Age - Sheehan, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
This paper looks at the development of Dublin City University (DCU), and at factors which have influenced the design of the new DCU Library, which is under construction and will be completed in July 2000. The library will be operational from September 2000.